A Packet Loss Concealment Technique Improving Quality of Service for Wideband Speech Coding in Wireless Sensor Networks - Nam In Park; Jin Ah Kang; Seong Ro Lee; Hong Kook Kim (International Journal of Distributed Sensor Networks)
A packet loss concealment (PLC) algorithm is proposed to improve the quality of decoded speech when packet losses occur in a wireless sensor network. The proposed algorithm is mainly based on artificial bandwidth extension (ABE) from narrowband to wideband. It consists of three main functions: packet loss concealment in the narrowband, ABE in the modified discrete cosine transform (MDCT) domain, and smoothing of wideband MDCT coefficients with those of the last good frame. The performance of the proposed PLC algorithm is implemented by replacing the PLC algorithm employed in the ITU-T Recommendation G.729.1. The experimental results show that the proposed PLC algorithm provides significantly better speech quality than the PLC in the ITU-T G.729.1.